Control Selection for RNA Quantitation. (August 2000) - Suzuki, Toshihide; Higgins, Paul J.; Crawford, Dana R.
The study of mammalian gene expression is often carried out at the level of mRNA. In such analyses, one usually measures the amount of an mRNA of interest under different conditions such as stress, growth, development, cell and tissue localization or as part of an evaluation of the effects of gene transfection. A variety of techniques exist to measure gene expression and most commonly involve Northern hybridization analysis, ribonuclease protection or RT-PCR. Common to all of these assays is the inclusion of a so-called loading or internal control (i.e., analysis of an mRNA that does not change in relative abundance during the course of treatments). Here, we discuss the uses and pitfalls of the most popular of these controls, glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and β-actin, with special emphasis on precautions associated with the use of GAPDH.